Determining polarity distribution of atmospheric water-soluble organic matter - Lee, Wen-Chien (2019)
Organic matter (OM) accounts for a significant fraction of submicron particulate in the atmosphere. The impact of OM on climate and human health is largely contributed by the water-soluble OM (WSOM). Interplay of WSOM and water leads to hygroscopic growth and cloud formation processes. Magnitude of the organic hygroscopicity can be determined by the polarity distribution of WSOM, yet experimental method to systematically examine the relationship is not available. This thesis presents a novel framework to classify WSOM according to its 1-octanol−water partition coefficient (KOW), which often serves as a metric of polarity and water solubility. Fractionization of OM by the KOW approach offers information about the degree of oxidation, which has been viewed as a critical indicator in governing the thermodynamic properties of OM. A theoretical method was developed to classify WSOM by varying the volume ratio of 1-octanol and aqueous phases and extraction steps. An inversion algorithm was further developed to derive KOW distribution of WSOM. The method was verified by OM from proxy of biomass burning particles, and applied to Indonesian biomass burning particles. Optical and chemical characteristics of the extracted WSOM were measured by UV−visible spectrophotometer, spectrofluorometer, and aerosol mass spectrometer. Deconvolution methods including positive matrix factorization, parallel factor analysis, and least-squares analysis were applied to the measured spectra, categorizing WSOM into three classes. The highly polar fraction of WSOM (log KOW < 0) is dominated by highly oxygenated species; the marginally polar fraction (0 ≤ log KOW ≤ 1) likely contains aromatic compounds; while the least polar fraction (log KOW ≥ 1) mostly consists of hydrocarbon-like species. Comparison with hygroscopicity measurements indicates that only WSOM in the highly polar fraction (log KOW < 0) can significantly contribute to water uptake.